Otorita Batam dan Reformasi Sistem Pemerintahan di Indonesia (1997-2004) - Muchid Albintani; Ali Yusri; Ishak (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2011)
Otorita Batam is a New Order institution ( assumed ORBA) still deputize regime of otoritarian Soehartowith three especial activity namely economics, political and inseparable law. System governance reformUUD 1945 cannot give impact to existence of Otorita Batam and make product institute of ORBA thisremain to be strong as a self-supporting institution. This research aim (i). Analysing and explainingposition of Otorita Batam at reform era in system governance of Indonesia. ( ii) Identify and factorsformulation causing the increasing of independence power of Otorita Batam reform execution era of areaautonomy in Indonesia. This research use approach of political and political economics of law. ThisResearch type qualitative. Method data collecting research of field, circumstantial interview anddocumentation with informan. While method analyse data use analytical discriptioin. Result of researchget, (i) The actor or importance group maintaining existence of Otorita Batam in system governance ofIndonesia. That is why policy of Otorita Batam which only in the form of Decision of President remain tobe defended, even contradiction and weaker than law. Whereas, cause factors gain strength of OtoritaBatam era execution of decentralization (local autonomi) caused its strong (ii) Domicile power of CentralGovernment and weaken law him Governance of Area and Otorita Batam at variance with LocalGovernment. Both this factor show if institute made in this ORBA represent the part of regime ofotoritarian which remain ( Neo-Soehartois). This reality bear term which is on a period of ORBA referredas ' state in state' and reform era referred as with ' state in local gorvernment'.Keywords: Otorita Batam, local autonomy and reformation